The tension of metaphysical and post-metaphysical political philosophies in Greece - Mansour Mirahmadi; Farzad Nemati (رهیافتهای سیاسی و بین المللی)
Post-metaphysical thinking, as a criticism of the metaphysical tradition of Western philosophy, spread in the second half of the 20th century, and some have considered this as a sign of a break with the ancient Greek tradition. The problem of this article is the hidden post-metaphysical possibilities in the Greek philosophical tradition, and for this purpose, an attempt has been made to show that not only cannot He considered the whole Greek tradition to be metaphysical, but there are some components of post-metaphysical thinking such as situated rationality, the priority of action over theory and paying attention to the metaphorical aspect of language in the thought of Greek epic and tragic poets, sophists and Aristotle. The importance of such attention is that the contextualist interpretation of the texts shows that along with the maturity of metaphysical objective wisdom in Greece, there are also streaks of competing subjective and rhetorical wisdom in the thought of some Greek thinkers and therefore the tension between metaphysics and post-metaphysics which reached its peak in the 20th century. The receipt itself was included in the conditions of the establishment of philosophy and in the system of philosophical knowledge of Greece; This can be tested specifically in Aristotle's criticism of the Platonic parable theory and his philosopher-king theory by using the teachings of epic writers, tragedians and sophists.